Safety and Tolerability of ShigActive™, a Shigella spp. Targeting Bacteriophage Preparation, in a Phase 1 Randomized, Double-Blind, Controlled Clinical Trial - Wilbur H. Chen; Joelle Woolston; Silvia Grant-Beurmann; Courtney K. Robinson; Garima Bansal; Joseph Nkeze; Jasnehta Permala-Booth; Claire M. Fraser; Sharon M. Tennant; Mallory C. Shriver; Marcela F. Pasetti; Yuanyuan Liang; et al. (MDPI AG, 2024)
Bacterial diseases of the gastrointestinal (GI) tract continue to be a major worldwide cause of human morbidity and mortality. Among various enteric pathogens, Shigella spp. are some of the most common and deadly bacterial pathogens. They are responsible for ~125 million worldwide cases of shigellosis, and ~14,000 deaths annually, the majority in children under the age of 5 and occurring in developing countries. Preventing and treating shigellosis with conventional drugs (e.g., vaccines and antibiotics) has proven to be very difficult. Here, we assessed the safety and tolerability of ShigActive™, a lytic bacteriophage preparation targeting Shigella spp., in a randomized, placebo-controlled, double-blind Phase 1 clinical trial. Ten participants randomized 4:1 received ShigActive™ or placebo co-administered with sodium bicarbonate orally three times daily for 7 days. Solicited and unsolicited adverse events (AEs) were observed for 29 days. Fifty percent of the subjects receiving ShigActive™ reported mild GI-related symptoms, while one participant experienced moderate fatigue. No serious or medically attended AEs occurred through day 90. Additionally, no significant differences in GI-associated inflammatory mediators or fecal microbiome changes were observed between placebo- and ShigActive™-treated subjects, or from a participants' baseline value. The results of this first-in-human (FIH) randomized, controlled Phase 1 trial of ShigActive™ demonstrate that it is safe and well tolerated when orally administered with no significant differences compared to placebo controls.